Ultrastructural and morphometric analysis of peripheral nerve regeneration within silicone tubes - Canpolat, Leyla; Kukner, Aysel; Canpolat, İbrahim; Ozan, Enver (My University, 1999)
Semi-thin and thin sections were used to observe the morphogenesis of peripheral nerves regenerating in silicone tubes. The progress of peripheral nerve regeneration across a 10 mm gap within the silicone tubes was examined after 3, 6 and 9 months. The left sciatic nerves of rats were transected. The proximal and distal nerve stumps were inserted into a silicone tube, in which they were separeted by a 10 mm gap. A tissue cable formed inside the silicone tube with regenerated axons. In the 3rd month, the 10 mm gap was bridged by a structure composed of regenerating axons, blood vessels and Schwann cells of a newly formed nerve trunk. After 3, 6 and 9 months the sciatic nerves regenerated. The endoneurial tissue continuity in the tubes was completely disrupted and the growth environment was completely reconstituted for regenerating fibers. In none of the experimental groups was degeneration observed in the myelinat-ed, unmyelinated or the endoneurial tissue. In the 9-month group, all myelinated and unmyelinated nerve fibers were normal, but the myelinated fiber diameter, myelin sheath thickness, axon diameter and myelinated axon number did not reach their normal values. Myelinated nerve fibers were normal in all of the groups, while the distal nerve part of only one animal was degenerated in the 3-month group.
Keywords: Rats; Nerve Regeneration; Microscopy; Electron; Peripheral Nerves